Manajemen Konflik Kebijakan Tata Tertib Sekolah Dalam Penanganan Pelanggaran Siswa Terlambat Masuk Sekolah Di SMA Negeri 1 Tamanan - Noval, Muhammad; .Ismail, Moh; Zuhro’ Fitriana, Ani Qotuz (CV. ITTC INDONESIA, 2023)
This research is focused on conflict management of school discipline policies carried out by the school to late students entering school. The background of the research is that there are many violations of the rules, especially in terms of being late for school. The research was conducted with the aim of knowing the factors of being late for school and the implementation of conflict management policies on school discipline in handling students late for school at SMA Negeri 1 Tamanan. The research conducted is descriptive qualitative, namely research that produces data in the form of descriptive or written or unwritten words from sources. Informants in the study were counseling teachers, student teachers, and 5 students who were often late for school at SMA Negeri 1 Tamanan. Data collection techniques using observation and interviews. As for the research results obtained, namely the factor of students entering school late comes from self factors and school discipline policy factors. The application of conflict management policies for school discipline in handling students late for school is by giving points, encouraging motorbikes and reprimands when entering class by the teacher who is teaching.